Hypofibrinogenaemia: A Case of Spontaneous Bleeding and Central Venous Thrombosis in the Same Lifetime - Soares, Adriana Watts; Maia, Maria; Santo, João Espirito; Costa, Ana Palricas; Pereira, Artur; Catarino, Cristina (European Journal of Case Reports in Internal Medicine, 2020)
The authors present the case of a 27-year-old patient who suffered from spontaneous bleeding during infancy and from a severe and central venous thrombosis in adult years. The patient underwent a thorough laboratory work-up on both occasions and was diagnosed with hypofibrinogenaemia as well as protein S deficiency, 2 diseases that contrast in their intrinsic bleeding/thrombotic risk. The patient´s high-risk pregnancy was carried out up to a successful full-term eutocic delivery which required fibrinogen concentrate to reduce life-threatening bleeding. The patient´s child was also diagnosed with hypofibrinogenaemia, later on confirmed with the pathogenic mutation Fibrinogen Marseilles II. This case was used to conduct a literature review of congenital fibrinogen disorders, rare entities that require more awareness for early diagnosis and accurate management.